Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

The patterns and driving forces of orbital-to millennial-timescales East Asian summer monsoon precipitation variations during the last glaciation - Yi Li; Jingwei Zhang; Xinmiao Chen; Zhi Zhang; Qingfeng Shao; Xinggong Kong; Simin Peng (CATENA, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Optimization of fertilization regimes for major crops in the Hetao Irrigation District based on the DNDC model and evaluation of economic benefits - Cong Hou; Haibin Shi; Yan Yan; Qingfeng Miao; Yi Zhao; Sihan Xue; Jiapeng Zhang; Weiping Li (European Journal of Agronomy, 2026)

Evolution of plumes from a composite plate–cylinder heat source under buoyancy–shear driven conditions - Ningbin Zhu; Yang Yang; Mengdan Qiao; Yi Wang; Qingfeng Cao; Yong Cui; Yuming Zhang; Sikang Li (Building and Environment, 2026)

Resistance characteristics of irregular exhaust hoods and inverse design based on airflow distribution in rolling mills - Qingfeng Cao; Yang Yang; Zhaolan Zhang; Yi Wang; Kangning Xiong; Yong Cui; Yuming Zhang; Sikang Li; Ning Lei (Journal of Cleaner Production, 2026)

Synergistic optimization of filter bag arrangement and shape for vortex suppression flow equalization and resistance reduction in a straight-through baghouse dust collector - Qingfeng Cao; Yang Yang; Yi Wang; Kangning Xiong; Ningbin Zhu; Yong Cui; Yuming Zhang; Sikang Li (Journal of Cleaner Production, 2026)

Pressure drop reduction of filter media for oily aerosol: progress and prospects - Yong Cui; Yang Yang; Kangning Xiong; Yi Wang; Qingfeng Cao; Sikang Li; Yuming Zhang (Energy and Buildings, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Diffusion of micron-sized oil droplets accompanying short-term thermal airflow with weak buoyancy in machining intervals - Yuming Zhang; Yang Yang; Yi Wang; Jia-ning Fan; Tongtong Zhao; Jun Gao; Qingfeng Cao; Ningbin Zhu; Yong Cui (Building and Environment, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

A physics-informed neural network integrating physical mechanisms and experimental data for predicting VOCs emission rates in machining workshops - Mengdan Qiao; Yang Yang; Ningbin Zhu; Yi Wang; Sikang Li; Qingfeng Cao; Yanghui Hou; Bo Qian (Building and Environment, 2025)

Nitrogen-doped graphite supported cobalt nanoparticles as excellent ORR/OER/HER trifunctional electrocatalysts - Wenxuan Fan; Xiangmei Tang; Qingfeng Yi; Guang Li (Fuel, 2025)

Evaporation and settling of semi-synthetic metalworking fluid droplets in industrial buildings - Yuming Zhang; Yang Yang; Qingfeng Cao; Ningbin Zhu; Yong Cui; Yi Wang; Chaojie Wang (Building and Environment, 2025)

Variations of Asian summer monsoon and regional hydroclimate between the MIS 7.1 and 6.5 - Xiumin Zhai; Jingwei Zhang; Yi Li; Yijia Liang; Kan Zhao; Qingfeng Shao; Yongjin Wang; Xinggong Kong (Global and Planetary Change, 2025)

Mechanism of photoluminescence properties of lyocell fibers changing with crystallinity - Xiaoping Lei; Qingfeng Wu; Xiangxi Zhang; Qing Zhou; Lingmin Yi (Carbohydrate Polymers, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

Spatial and temporal heterogeneity of soil salinity and ionic coupling relationship under the water-saving renovation of a typical irrigation district in arid and semi-arid areas - Shuya Yang; Qingfeng Miao; Haibin Shi; Yi Zhao; Xiaoyu Liu; Xin Nie; Weiying Feng; José Manuel Gonçalves; Tao Zhang; Yuxin Li; Yuli Luo (Science of The Total Environment, 2024)

Characterization of shale oil and water micro-occurrence based on a novel method for fluid identification by NMR T2 spectrum - Junjie Wang; Shuangfang Lu; Pengfei Zhang; Qingfeng Li; Yajie Yin; Wenbiao Li; Nengwu Zhou; Guohui Chen; Yangjian Yi; Chenxi Wu (Fuel, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Enhanced Asian hydroclimate instability during early MIS 6.5 - Dianbing Liu; Yongjin Wang; Xinggong Kong; Qingfeng Shao; Yi Li (Quaternary Science Reviews, 2024)

Optimization and control strategy of BOG re-liquefaction process for LNG vessels - Ting Guo; Lesheng Liu; Jiubing Shen; Qingfeng Jiang; Sichen Wu; Yanyan Zhou; Yi Liu (International Journal of Refrigeration, 2023)

Low-dose graphene oxide promotes tumor cells proliferation by activating PI3K-AKT-mTOR signaling via cellular membrane protein integrin αV - Zhiwen Zheng; Abuduliaizezi Halifu; Juan Ma; Leyi Liu; Qingfeng Fu; Bocun Yi; E. Du; Dawei Tian; Yong Xu; Zhihong Zhang; Jianqiang Zhu (Environmental Pollution, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Development of organic-inorganic hybrid antimicrobial materials by mechanical force and application for active packaging - Weizhong Zhu; Jiali Chen; Qingfeng Dong; Donglei Luan; Ningping Tao; Shanggui Deng; Li Wang; Yi Hao; Li Li (Food Packaging and Shelf Life, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Ice-volume and insolation influences on hydroclimate changes in central eastern China during the antepenultimate glacial period - Quan Wang; Shayue Yuan; Yijia Liang; Kan Zhao; Qingfeng Shao; Zhenqiu Zhang; Junji Zhu; Xinggong Kong; Yongjin Wang; Jianghu Lan; Hai Cheng; Chengwei Xia; et al. (Science China Earth Sciences, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Role of Melatonin in Inducing the Physiological and Biochemical Processes Associated with Heat Stress Tolerance in Tall Fescue (Festuca arundinaceous) - Mohammad Nur Alam; Li Yang; Xue Yi; Qingfeng Wang; Arif Hasan Khan Robin (Journal of Plant Growth Regulation, 2022)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Correction to: MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

MiR-96 promotes apoptosis of nucleus pulpous cells by targeting FRS2 - Xiaoxia Yang; Hengping Liu; Qingfeng Zhang; Kan Liu; Dong Yu; Yi Zhang; Zongting Shi (Human Cell, 2020)

The transcription factor VaNAC17 from grapevine (Vitis amurensis) enhances drought tolerance by modulating jasmonic acid biosynthesis in transgenic Arabidopsis - Lingye Su; Linchuan Fang; Zhenfei Zhu; Langlang Zhang; Xiaoming Sun; Yi Wang; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2020)

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Overexpression of VaWRKY12, a transcription factor from Vitis amurensis with increased nuclear localization under low temperature, enhances cold tolerance of plants - Langlang Zhang; Tingting Zhao; Xiaoming Sun; Yi Wang; Chang Du; Zhenfei Zhu; Duncan Kiragu Gichuki; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Molecular Biology, 2019)

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

Hepatic stellate cells produce vascular endothelial growth factor via phospho-p44/42 mitogen–activated protein kinase/cyclooxygenase-2 pathway - Yi Zhao; Yanqing Wang; Qiang Wang; Zhengrong Liu; Qingfeng Liu; Xin Deng (Molecular and Cellular Biochemistry, 2012)